BOLSA FAMÍLIA: IMPORTANTE DETERMINANTE PARA A EDUCAÇÃO E CRESCIMENTO SOCIOECONÔMICO DO BRASIL - Ferreira, Luiz Antonio (2012)
This study approaches a new and unexplored subject, the Brazilian Family Aid Program. Bibliography practically does not exist and academic entities seldom discuss the subject because it is still under development. References are found in lectures, newspapers and magazine articles. This is an exploratory and analytical search, approaching evidence basis and sources. The Programa Bolsa Família (PBF) is a Brazilian Family Aid Program granted under conditionality rules. It can be considered a unique tool for income distribution, working towards an effective solution for families surviving under extreme poverty. The program started by the merger of three other poverty aid programs of dubious effectiveness Scholarship Aid, Cooking Gas Aid and Food Card. The PBF benefits families surviving under poverty conditions, with R$ 70 to R$ 140 monthly of per capita income and under extreme poverty conditions, below R$ 70 monthly of per capita income. Also, the PBF establishes conditional participation rules associated to education and health prevention for children. Presently the PBF supports 13 million families that fit rules and are enrolled in the Cadastro Único (Central Control Registration Roll). That registration roll practically covers the totality of the population under poverty situation line as defined by PNAD - 2006 (National Household Survey - 2006).The PBF control methodology allows income transfer to regions left under poverty conditions in past history. The PBF formed a new consumer community, new entrepreneurs, moreover, attracted investors. In regard to education there is reduction in illiteracy. The Human Development Index (HDI) shows vegetative growth, Brazil is the 84th country ranked among the 187 nations controlled by the United Nations Development Programme (UNDP) in 2011. The dimensions that compose the index for Brazil had poor growth lately, in particular the expected years of schooling for children at school enrollment age (in Brazil, 6 years old) declined during the last decade (2000-2010). It is likely that there is a structural issue with the Brazilian education sector. There is a socio-economic growth in regions where poverty has been endemic, in particular Northeast Region. The findings also reveal migration reversal that in past were North/Northeast Regions to Southeast Region as well as fecundity rate reduction, which are remarkable advantages. Brazil entered into the demographic bonus , a situation when the economically active population exceeds the dependent population , this is also an advantage because attracts investments and is a push towards economic growth. Despite of positive improvements, they appear to be insufficient, the human development in Brazil is far from excellence, presently a HDI of 0,718, with a growth of 0,769% annually (2000-2010) it will take 35/36 years to meet the Australian HDI of 0,943%. Unless chances help us, dreams to join the winners are unlikely. The Programa Bolsa Família , however, proves to be a social front towards inequality; the participants of the plan, originally classified under poverty line were rescued.